Exploring cultural logic in becoming teacher: a collaborative autoethnography on transnational teaching and learning. Issue 2 (27th May 2021) - Kim, Taeyeon; Reichmuth, Heather L.
ABSTRACT: Departing from the view that learning is a linear progression, we argue that through the lens of cultural historical activity theory (CHAT) and cultural logic, teacher learning research can be advanced. Applying these two constructs to a collaborative autoethnography of two emerging scholars' transnational teaching and learning experiences in the US and South Korea we argue that implicit and explicit norms in a culture influence the process of becoming teacher in the Korean context. Findings suggest that socio-cultural elements of implicit beliefs and norms outside of schools are linked to teacher learning inside schools, thereby suggesting that teacher learning at the micro-level needs to be understood alongside meso-level artefacts and macro-level factors in the complex process of becoming teacher. This study supports the view that becoming teacher is nonlinear and culturally situated.